Comparison and Selection of Channel Desilting Schemes Based on Hydrodynamic Models - TONG Yu; JIA Jinrui; HOU Jingming; JING Jing; ZHANG Fan; ZHOU Qingshi; WANG Tian; LIU Yuling (Renmin Zhujiang)
In order to explore the desilting effects of different channel desilting schemes, a hydrodynamic model accelerated by a graphic process unit (GPU) was used to construct a flood evolution model for the study area and simulate the flood inundation situation of the channels in the study area after implementing four desilting schemes at different return periods. The results show that: ① The schemes in terms of flood inundation alleviation and desilting excavation volume in descending order are as follows: full-section scheme, combination scheme, only floodplain scheme, and only thalweg scheme. ② The inundated area of each scheme decreases by 4.20%~21.68%, 1.57%~13.85%, 6.66%~43.6%, and 5.63%~39.7%, respectively. In terms of inundated area reduction rate, the combination scheme has an average reduction of 2.19% compared with the full-section scheme at different return periods, but the excavation volume of the full-section scheme is 21.89% higher than that of the combination scheme. ③ The ratio of the inundated area reduction rate to the excavation volume is used to represent the ability to reduce the inundated area per unit excavation volume. The ability of each desilting scheme to reduce inundated area is 7.34%~12.49%, 2.75%~7.98%, 8.86%~19.08%, and 9.13%~21.18%, respectively. The combination scheme has the strongest ability to reduce the inundated area at different return periods. Therefore, the combination scheme is determined as the comprehensive optimal scheme among the four desilting schemes. This study can provide a reference for channel desilting, flood control, and disaster reduction.